1959
DOI: 10.1093/clinchem/5.5.465
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Hyaluronic Acid in Synovial Fluid

Abstract: 1. The concentration of hyaluronic acid in synovial fluid was determined by a modification of the Dische carbazole method for the determination of uronic acids. 2. The results of this determination in 80 specimens of normal and abnormal synovial fluid confirmed values reported by other methods. 3. An inverse relationship between the hyaluronic acid in the synovial fluid and the degree of synovitis was suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

1966
1966
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…Aggregation by hyaluronic acid was not inhibited by these sulfhydrylinhibiting reagents and was demonstrable only after the gamma globulin was first thermally denatured. In normal synovial fluid the average concentration of hyaluronic acid is 2.3 to 4.1 mg/ml, but in synovial fluid from patients with rheumatoid arthritis the concentration of hyaluronic acid may be less (0.7 to 1.2 mg/ml) (8,16,21). T h e amount of hyaluronic acid in a rheumatoid joint, however, is often increased (16) because the increase in volume of rheumatoid synovial fluid often overcompensates for the decrease in concentration of hyaluronic acid found in this disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Aggregation by hyaluronic acid was not inhibited by these sulfhydrylinhibiting reagents and was demonstrable only after the gamma globulin was first thermally denatured. In normal synovial fluid the average concentration of hyaluronic acid is 2.3 to 4.1 mg/ml, but in synovial fluid from patients with rheumatoid arthritis the concentration of hyaluronic acid may be less (0.7 to 1.2 mg/ml) (8,16,21). T h e amount of hyaluronic acid in a rheumatoid joint, however, is often increased (16) because the increase in volume of rheumatoid synovial fluid often overcompensates for the decrease in concentration of hyaluronic acid found in this disease.…”
Section: Discussionmentioning
confidence: 98%
“…that the reported beneficial effects of gold thiomalate, D-penicillamine, and L-histidine (4,5) in patients with rheumatoid arthritis are related to the ability of these compounds to inhibit the sulfhydryl-mediated thermal aggregation of human gamma globulin (6). Since rheumatoid arthritis is mainly a disease of diarthroidal synovial joints and since synovial fluid has the largest concentration of hyaluric acid in the human body (8)(9)(10)(11) as well as substantial amounts of gamma globulin (12,13), the present study was undertaken to determine the effect of hyaluronic acid on the thermal aggregation of human gamma globulin.…”
mentioning
confidence: 99%
“…HAs exhibit unique viscoelastic properties with highly non-Newtonian characteristics that allow the synovial fluid to provide the fluid dynamic properties of lubrication, as well as resistance to compression and shear forces. [9,10] Healthy synovial fluid is primarily composed of HA of high molecular weight, but during the development of OA the concentration of HA drops and the average polymer length (normal molecular weight of 3-4 million Daltons [11]) degrades, which markedly impacts the viscoelastic properties of the synovial fluid. HA therapy is intended to temporarily restore the rheology of the synovial fluid toward its healthy state.…”
Section: Open Accessmentioning
confidence: 99%
“…13 These parameters decrease in pathological SF. 1,14 Oates et al 15 showed that protein aggregation provides SF with the rheopectic behaviour. The common result of studies on the composition of normal and pathological SF showed that in pathological SF (compared to normal SF), both concentration and molecular weight of HA decreased and the proportionality of the HA concentration to the protein also changed.…”
Section: Introductionmentioning
confidence: 99%